Вилла на холме: Эшенден, или Британский агент: Рассказы / С. Моэм - Моэм С. (Республика, 1992)
Экземпляры: ф.4 (1992) / Инвентарный номер: 28855 / Цена: 55.00 / Сис.шифр: И / Авт.знак: М87 / ББК: 84(4Вел)